Filtrasi limbah batik Kutawaru Cilacap menggunakan fly ash yang diaktivasi asam sulfat - Manasikana, Arina; Ramadhani, Arnesya (Jurnal Rekayasa Proses, 2025)
The batik industry is one of the largest contributors to liquid waste. Batik liquid waste if not treated properly has the potential to increase disease and pollute the environment. Pollutant levels contained in the waste can be degraded by using fly ash as an adsorbent. Fly ash is obtained from Steam Power Plant waste. The purpose of this study was to determine the best concentration of sulfuric acid between 1M and 3M added to activate fly ash to reduce COD, BOD, TSS, color change and pH of Kutawaru batik waste. The research consisted of three stages: the first stage was the activation of fly ash by immersing it in a solution of 1M and 3M sulfuric acid with a ratio of 1:5 for 3 hours. Then, wash with water until the pH is neutral. Furthermore, the fly ash was dried using an oven at 105oC for 4 hours to a constant weight, resulting in sulfuric acid-activated fly ash. The second stage of the adsorption process, where batik waste was mixed with sulfuric acid-activated fly ash in a ratio of 5:1 for 3 hours, resulted in the waste after adsorption. In the last stage, testing of the waste before and after adsorption was carried out at the Cilacap Environmental Laboratory. The results showed that the best concentration of sulfuric acid for the activation of fly ash was 1M because it reduced COD, BOD and TSS by up to 90%. Changes in COD, BOD, TSS, color and pH of batik waste before and after adsorption using 1 M sulfuric acid-activated fly ash, namely COD 13678 mg/L to 1302 mg/L, BOD 8480 mg/L to 870 mg/L, TSS 460 mg /L becomes 47 mg/L, the color of the batik waste changes from black to yellow, and pH 9 becomes 7.